Implementation of Active Learning Methods in Islamic Religious Education to Improve Students' Critical Thinking Skills in Schools - Nur Hidayati (Universitas Nurul Jadid, 2024)
This research aims to examine the effectiveness of implementing active learning methods in Islamic Religious Education (PAI) as an effort to improve students' critical thinking skills at school. This research uses a quantitative approach with a quasi-experimental design, involving students from several secondary schools as samples. Data was collected through critical thinking skills tests before and after implementing active learning methods. The research results show that the application of active learning methods significantly improves students' critical thinking skills in the PAI context. These findings indicate that this method is effective in creating a learning environment that supports the development of students' analytical, evaluation and reflection skills on religious values, as well as their relevance in everyday life.